HUBUNGAN PERSONAL HYGIENE DAN SANITASI LINGKUNGAN DENGAN KELUHAN PENYAKIT KULIT DI KELURAHAN DENAI KECAMATAN MEDAN DENAI KOTA MEDAN TAHUN 2012 - Agsa Sajida; Devi Nuraini Santi; Evi Naria (Lingkungan dan Kesehatan Kerja, 2013)
The relation of personal hygiene and environmental health with skin disease in Denai District Medan Denai Subdistrict. Skin is a part of body that quite sensitive for kind of diseases. Bad environment intended some of skin diseases. Factors to influence high of prevalance skin diseases are warm climate and hubidity, bad personal hygiene such as cleanliness of skin, hair, skin of the head, nails, intensity of take a bath and decrease economic is also factor to influence.The Purpose of this analytical survey study with cross sectional design was to analyze the relationship between personal hygiene (cleanliness of skin, hands and nails, clothes, towels, bed and bed linen and environmental sanitation with remonstrance of skin diseases at Denai district Medan Denai Subdistrict Medan city in 2012.Kind of this research is analytical survey with cross sectional study design. Population of this study were all of people in this area with criteria as a female 10-14 years old. Total of that criteria were 743 people and sampel of this study were 88 people.The result of this study found that the most of cleanliness of skin, hands and nails and towel were bad category, whereas cleanliness of clothes, bed and bed linen were good category. Test result showed that there was a significant relationship between cleanliness of skin (p=0,009), hands and nails (p=0,001), clothes (p=0,011), towels (p=0,001), bed and bed linen (p=0,025), environmental sanitation (p=0,014) with skin diseases remonstrance.The management of cadres in community health center is suggested to provide further information about remonstrance skin diseases through extension and training in Denai district Medan Denai Subdistrict Medan City and community need for improving personal hygiene and protect environmental health hope that can out of skin diseases. Key words: Skin diseases, Personal Hygiene, Environmental sanitation